Investigation of sodium borohydride production process: Wexite mineral as a boron source - Piskin, Mehmet Burcin (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Currently, the energy requirements of the entire world are mostly provided by hydrocarbon-based fossil fuels, such as coal, fuel oil, or natural gas. Because of environmental pollution, decrease in energy sources, and difficulties in storing electricity, more attention is dedicated to new sources of energy, such as hydrogen. Presently, sodium borohydride (NaBH(4)) appears to be an excellent hydrogen-storage medium due to its high theoretical hydrogen yield by weight, 10.6%. The main aim of the present study is to investigate NaBH(4) production from ulexite mineral (NaCaB(5)O(9)center dot 8H(2)O). The experimental investigation consists of four steps, such as (1) Characterization of NaCaB(5)O(9)center dot 8H(2)O by X-ray diffraction, differential thermal and thermogravimetric analysis, scanning electron microscopy, and attenuated total reflectance of Fourier-transform infrared spectroscopy; (2) Preparation of ulexite-borosilicate glass (NaCaB(5)O(9)center dot SiO(2)); (3) Synthesis of NaBH(4) from ulexite-borosilicate glass; and (4) Separation of NaBH(4) from the reaction mixture. NaBH(4) can thus be produced by heating ulexite mineral form of borosilicate glass with metallic sodium under 3-atm. hydrogen pressure at 450-500 degrees C for 4 h. (C) 2009 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen energy; Storage; Sodium borohydride; Ulexite mineral; ALKALINE-SOLUTION; HYDROGEN; ENERGY; HYDROLYSIS; CATALYST; NABH4; Chemistry; Electrochemistry; Energy & Fuels